Dribbling Skill Level in Football Game - Handoko Sejahtera Sigalingging; Dicky Hendrawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research was carried out with the aim of knowing the level of dribbling skills in the soccer game of class X students of SMK Negeri 1 Siatas Barita Kab. North Tapanuli Academic Year 2020/2021. The subjects in this study were students of class X, amounting to 27 people. This research is a quantitative descriptive study that is about students' dribbling skills, meaning that in this study researchers only wanted to know the level of dribbling skills of class X students at SMK Negeri 1 Siatas Barita Kab. North Tapanuli for the 2020/2021 Academic Year, where the data is in the form of numbers in seconds. The results showed that the level of dribbling skills of class X SMK Negeri 1 Siatas Barita Kab. North Tapanuli for the 2020/2021 Academic Year are as follows: there are no students (0%) who are included in the